Investigating Seasonal Anomalies and Volatility Patterns for Brazilian Securities Markets - Pandey, Asheesh; Mittal, Arjun; Singh, Madan (Indian Journal of Finance, 2024)
Purpose : The goal of the study was to find out if Brazilian stock markets had any notable calendar abnormalities. The study’s goal was to determine whether volatility clustering exists and how it responds to both positive and negative shocks to Brazil’s capital market. Methodology : The emerging markets information services database was used to obtain the closing prices of nine Brazilian stock indices from 2012 to 2022. Four well-known calendar anomalies were examined using the dummy variable regression approach: the trading month effect, Halloween impact, day of the week effect, and month of year effect. GARCH-based models, including GARCH-M and T-GARCH techniques, have subsequently been used to conduct tests on the nature of volatility clustering. Findings : The results proved that there is volatility clustering. For Brazil, the only noteworthy anomaly found was the month-of-the-year effect, which indicates that the sample indices only showed meaningfully positive returns in April. Finally, the results showed that, in contrast to positive shocks, negative shocks exhibited more pronounced clustering throughout the second moment. Practical Implications : The study has implications for regulators and market players. While market participants might use this anomaly to develop profitable trading strategies for Brazil, authorities can investigate whether calendar oddities are caused by regulatory inefficiencies or issues with microstructure. Originality : This certifies that the study paper was created by the authors independently and entirely of their own ideas.